Synthesis and characterization of bis(4-amino-2-bromo-6-methoxy)azobenzene derivatives - Martínez-López, David; Babalhavaeji, Amirhossein; Sampedro, Diego; Woolley, G. Andrew (Beilstein Journal of Organic Chemistry, 2019)
Aminoazobenzene derivatives with four ortho substituents with respect to the N–N double bond are a relatively unexplored class of azo compounds that show promise for use as photoswitches in biology. Tetra-ortho-methoxy-substituted aminoazobenzene compounds in particular can form azonium ions under physiological conditions and exhibit red-light photoswitching. Here, we report the synthesis and characterization of two bis(4-amino-2-bromo-6-methoxy)azobenzene derivatives. These compounds form red-light-absorbing azonium ions, but only under very acidic conditions (pH < 1). While the low pKa makes the azonium form unsuitable, the neutral versions of these compounds undergo trans-to-cis photoisomerization with blue-green light and exhibit slow (τ1/2 ≈ 10 min) thermal reversion and so may find applications under physiological conditions.
Keywords: azobenzene; azonium; molecular switches; ortho substitution; photoisomerization; photoswitch; visible light